2017
DOI: 10.1111/head.13235
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Migraine and Suicidal Behaviors: A Nationwide Study in the USA

Abstract: Chronic conditions that do not affect the current hospitalization may not have been reported. The presence of psychiatric diagnoses influences associations of suicidal behaviors with migraine in a national inpatient sample. Migraineurs with diagnosed comorbid psychiatric disorders may be receiving care that mitigates their risk for suicidal behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…Migraine may be associated with increased risk of suicidal ideation or behavior as reported by several studies [ 8 , 9 , 37 ]. In the current study, nearly 17% of the patients had comorbid depression, but treatment-emergent suicidal behavior was not reported.…”
Section: Discussionmentioning
confidence: 98%
“…Migraine may be associated with increased risk of suicidal ideation or behavior as reported by several studies [ 8 , 9 , 37 ]. In the current study, nearly 17% of the patients had comorbid depression, but treatment-emergent suicidal behavior was not reported.…”
Section: Discussionmentioning
confidence: 98%
“…Operationalizing income status via method of payment for services-specifically Medicaid as a proxy for low-income status-is an established approach in the literature (e.g., Buck, Msall, Schisterman, Lyon, & Rogers, 2000;Hurt & Betancourt, 2015;Marcin, Schembri, & Romano, 2003;Schechter & Margolis, 1998) and has been used in studies utilizing HCUP data (e.g., Albrecht et al, 2010;Correa, Bardenheier, Elixhauser, Geiss, & Gregg, 2015). Based on previous studies, the analysis also controlled for multiple covariates (e.g., Correa et al, 2015;Friedman, Zhong, Gelaye, Williams, & Peterlin, 2018;Jinjuvadia et al, 2018), including age (continuous), urbanicity of patient (1 = central urban, 2 = suburban, 3 = exurban, 4 = rural, 5 = micropolitan, 6 = other), and hospital region of the county (1 = Northeast, 2 = Midwest, 3 = South, 4 = West).…”
Section: Methodsmentioning
confidence: 99%
“…[88][89][90][91] SM may also increase the risk of suicidality. [88][89][90][91] SM may also increase the risk of suicidality.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Studies in both the adult and pediatric population suggest a link between migraine and suicidal behavior, with an increased association seen in those with chronic migraine and migraine with aura. [88][89][90][91] SM may also increase the risk of suicidality. A population-based study of adult Taiwanese patients diagnosed with either SM (n = 13,605) or migraine (n = 21,485) found that those with SM had a 1.81-fold risk of attempting suicide compared to a control group that did not have either diagnosis.…”
Section: Expert Opinionmentioning
confidence: 99%